An overview of advances in glass ionomer cements - Saridena, Udaya Sri Naga Gayatri; Sanka, Gnana Siva Sai Jayalaksmi; Alla, Rama Krishna; Ramaraju, Alluri Venkata; Sajjan MC, Suresh; Mantena, Satyanarayana Raju (International Journal of Dental Materials, 2022)
Glass-ionomer dental cements (GICs) are aesthetic direct restorative materials with anticariogenic activity. Glass-ionomers are composed of alumino-silicate glass powder and poly acrylic acid liquid. The significant characteristics of GICs among restorative materials are their ability to bond to moist tooth structure without any pre-treatment and to provide a prolonged period of fluoride release, which prevents subsequent tooth decay (caries). These characteristics, along with the materials' acceptable aesthetics and biocompatibility, make them popular and desirable for use in medical and dental applications. However, GICs exhibit poor mechanical qualities and moisture sensitivity. To improve their mechanical and physical qualities, the GIC powders have undergone extensive formulation and modification. This paper provides an overview of various fillers used to enhance the mechanical and physical properties of GICs.